The impact of technological risk perception on consumer experience with digital curiosity as a moderating variable - Laksmi P, Kadek Wulandari; Putra P, Komang Widhya Sedana; Ariwangsa, IGN Oka (Privietlab, 2025)
In the advanced digital age, consumers engage with new technological interfaces that provide value in the form of personalization, convenience, and efficiency while exposing them to possible threats such as data insecurity, privacy breaches, and system failures. These opposing threats highlight the importance of understanding how consumers perceive technology-related risks and how this perception impacts their psychological experiences. Although the technology acceptance model and user satisfaction have been extensively studied, little is known about the psychological variables—particularly the construct of digital curiosity—that buffer perceptions of risk associated with technology. This study aims to fill this void by analyzing the effect of technological risk perception on consumer experience and the role of digital curiosity in this relationship. A quantitative approach involved using a structured questionnaire distributed to active digital consumers on different online platforms. Data analysis was performed using SmartPLS 4.0. The measurement model attained satisfactory validity and reliability. It was established that perceived technological risk negatively impacts the consumer experience. This suggests that a higher perceived risk correlates with diminished satisfaction, trust, and emotional ease. Among other variables, digital curiosity positively impacted consumer experience and interacted in such a way as to lessen the negative influence of perceived technological risk. This suggests that curiosity may serve as a psychological buffer that allows consumers to emotionally reconcile with technological risks, enabling them to retain a positive experience in situations where technology imposes a high risk. These findings indicate the need for organizations to offer digital experiences that provide a level of assurance concerning security while simultaneously fostering curiosity. Allowing exploration and more interactive engagement may help users navigate and trust more complex technological systems. The model proposed in this study may provide the basis for future studies to include additional variables, such as technostress and digital self-efficacy, to capture a more comprehensive theoretical perspective.